Operations research: an introduction - Taha, Hamdy A. (New York: Macmillan, 1992)
Operations Research provides a broad focus on algorithmic and practical implementation of Operations Research (OR) techniques, using theory, applications, and computations to teach students OR basics. The book can be used conveniently in a survey course that encompasses all the major tools of operations research, or in two separate courses on deterministic and probabilistic decision-making. The author preserves classical algorithms by providing essential hand computational algorithms as an important part of OR history. Based on input and submissions from OR students, professors, and practitioners, the author also includes scenarios that show how classical algorithms can be beneficial in practice. These entries are included as Aha! Moments with each dealing with stories, anecdotes, and issues in OR theory, applications, computations, and teaching methodology that can advance the understanding of fundamental OR concepts.
Decision making in operations research -- Linear programming: formulations and graphical solution -- Linear programming: the simplex method -- Linear programming: revised simplex method -- Linear programming: duality, sensitivity, and parametric analysis -- Linear programming: transportation model -- Linear programming: additional topics -- Network models -- Integer linear programming -- Dynamic (multistage) programming -- Data representation in operations research -- Decision theory and games -- Project scheduling by PERT-CPM -- Inventory models -- Queueing models -- Queueing theory in practice -- Simulation modeling with SIMNET II -- Markovian decision process -- Classical optimization theory -- Nonlinear programming algorithms -- Review of vectors and matrices -- Software (TORA and SIMNET II) installation and execution
Includes index
Keywords: Operations Research